2003
DOI: 10.1046/j.1538-7836.2003.00070.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of ADP and ATP receptor expression in human platelets

Abstract: Summary. The mechanism of ADP-mediated platelet activation has been difficult to unravel due to the large number of receptors for extracellular nucleotides (P2 receptors). mRNA levels in circulating platelets are very low, but have been shown to be translationally active. By optimizing mRNA extraction and using real time (RT)-PCR we were able to establish a protocol for highly sensitive platelet mRNA quantification in human regular blood samples. In platelets from healthy volunteers, only P2X 1 , P2Y 1 and P2Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
71
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 31 publications
4
71
0
Order By: Relevance
“…The oligomeric association of P2Y12 receptors at the plasma membrane was shown to depend on disulfide bond formation as demonstrated by the sensitivity of these complexes to DTT reduction after cell solubilization. This finding indicated that the P2Y12 receptor appears to behave in a similar way as ␤2AR in response to thiol-reducing agents, unlike P2Y1 receptors, which oligomers are resistant to reducing reagents (64). In contrast to some other GPCRs (3-13), the oligomerization of P2Y12 does not seem to be modulated by agonist binding, 2MeS-ADP being ineffective in changing the P2Y12 size distribution (data not shown).…”
Section: Discussionmentioning
confidence: 87%
“…The oligomeric association of P2Y12 receptors at the plasma membrane was shown to depend on disulfide bond formation as demonstrated by the sensitivity of these complexes to DTT reduction after cell solubilization. This finding indicated that the P2Y12 receptor appears to behave in a similar way as ␤2AR in response to thiol-reducing agents, unlike P2Y1 receptors, which oligomers are resistant to reducing reagents (64). In contrast to some other GPCRs (3-13), the oligomerization of P2Y12 does not seem to be modulated by agonist binding, 2MeS-ADP being ineffective in changing the P2Y12 size distribution (data not shown).…”
Section: Discussionmentioning
confidence: 87%
“…1,2 Extracellular ATP in the circulation is rapidly degraded into ADP, AMP, and adenosine by ectonucleotidases. 3 ATP and ADP activate P2 receptors on endothelium, platelets, 4,5 and other blood cells, 6 regulating several physiological responses including vascular tone, 7 platelet aggregation, and the release of endothelial factors. At least 15 nucleotide-activated cell surface receptors (7 of P2X and 8 of P2Y) have been found in man, with remarkably broad and varied physiological responses.…”
mentioning
confidence: 99%
“…P2Y 11 mRNA levels in platelets were reported to be much lower than those of P2Y 1 , P2Y 12 , and P2X 1 , although the level of mRNA depends on both its synthesis and degradation rates and may not linearly correlate with its protein expression (34). Also in human granulocytes, P2Y 11 mRNA is present at lower levels compared with mRNA of other purinergic receptors (40).…”
Section: Discussionmentioning
confidence: 97%
“…6A; control, n ϭ 5, p Ͻ 0.05). The only purinergic receptor known to stimulate adenylic cyclase is P2Y 11 (10,33), which is also expressed in human platelets (34). Preincubation of platelets for 30 min with 1 M NF157, a specific inhibitor of P2Y 11 (35), reduced cAMP overproduction induced by P18, P24, and Ap2A by ϳ70, 75, and 100%, respectively (Fig.…”
Section: Tablementioning
confidence: 93%